2021
DOI: 10.1055/s-0041-1731451
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk and Breastfeeding of Infants Born to SARS-CoV-2 Positive Mothers: A Prospective Observational Cohort Study

Abstract: Objective There are limited published data on the transmission of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus from mothers to newborns through breastfeeding or from breast milk. The World Health Organization released guidelines encouraging mothers with suspected or confirmed COVID-19 to breastfeed as the benefits of breastfeeding outweighs the possible risk of transmission. The objective of this study was to determine if SARS-CoV-2 was present in the breast milk of lactating mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…WHO guidelines encourage mothers with suspected or confirmed COVID-19 positive illness to breastfeed as the health benefits of breastfeeding outweigh the possible risk of transmission of COVID-19 ( 14 ). Studies have reported the presence of IgG and IgA SARS-COV-2 antibodies in the breast milk of women who tested positive for COVID-19 which may protect the neonate from postnatal infection ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…WHO guidelines encourage mothers with suspected or confirmed COVID-19 positive illness to breastfeed as the health benefits of breastfeeding outweigh the possible risk of transmission of COVID-19 ( 14 ). Studies have reported the presence of IgG and IgA SARS-COV-2 antibodies in the breast milk of women who tested positive for COVID-19 which may protect the neonate from postnatal infection ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence of SARS-CoV-2 transmission through breastmilk, with most studies reporting breastfeeding as a safe and recommended practice. 9 61 72 A recent systematic review looking at the transmission of SARS-CoV-2 through breastmilk and breastfeeding found no evidence of SARS-CoV-2 transmission through breast milk. 73…”
Section: Evidence Assessing the Safety Of Breastfeeding And Breast Milkmentioning
confidence: 99%
“…Standard recommendations during the COVID-19 epidemic suggest that who test positive mothers can feed their babies with infection control and prevention measure. [78][79][80][81][82][83] If the mother-baby dyad test positive for COVID-19, breast feeding is not contraindicated. 84 If both the mother and her newborn are hospitalized and separated from each other, expressed breast milk can be given.…”
Section: Importance Of Human Milk Bank In Covid-19 Pandemicmentioning
confidence: 99%
“…84 If both the mother and her newborn are hospitalized and separated from each other, expressed breast milk can be given. 79 If there is an HMB, expressed HM can be stored and will be able to provide milk to her own baby. 85…”
Section: Importance Of Human Milk Bank In Covid-19 Pandemicmentioning
confidence: 99%